PENERAPAN MEDIA FILM “NUSSA DAN RARA” PADA MATA PELAJARAN PENDIDIKAN PANCASILA FASE A DI SDN SUMUR WELUT III/440 SURABAYA - Shinta Ika Wati; Rarasaning satianingsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The animated film Nussa and Rara is a communication medium in the form of cartoon-style images or more precisely depicted cartoon characters which are very effective in conveying ideas in a unique way to provide inspiration, and also contains Pancasila education material, especially for elementary school students. This research aims to describe the extent to which Phase A teachers and students at SDN Sumur Welut III/440 Surabaya are able to apply the film media "Nussa and Rara" and to determine the feasibility of the film media "Nussa and Rara" which was developed in the Pancasila Education Subject. Phase A. This research uses a qualitative method with a descriptive approach where this approach describes the results of teacher activities and student activities in the Pancasila Education Subject Phase A. The subjects of this research were 1 teacher and 29 students. Data collection techniques in this research used observation, interviews and documentation sourced from purposive sampling techniques. The data analysis technique in this research is through data reduction, data presentation, and drawing conclusions. The validity of this research data is through a credibility test using triangulation techniques.